1995
DOI: 10.1029/95gl00169
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cosmic‐ray production of 10Be coincident with the Mono Lake and Laschamp Geomagnetic Excursions

Abstract: The cosmogenic isotope 10Be, total Be, and Al were measured in partly varved sediments from the upper 50 m of core 480, leg 64 (DSDP), Gulf of California. The concentration of 10Be from 1 to 50 kyr is in general agreement with estimates of the geomagnetic dipole moment obtained from archaeomagnetic and marine core research. 10Be anomalies were also found at 32 kyr and 43 kyr, contemporaneous with the Mono Lake and Laschamp excursions, respectively. The production of 10Be required to explain these anomalies is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…In recent years, time-dependent models of the main geomagnetic ®eld going back to 1690 have been produced (Bloxham and Jackson, 1992), using which, long term (b 10 2 y) variations in cuto rigidities of cosmic rays can be computed. Enhanced cosmic ray production of 10 fe coincident with the Mono Lake and Laschamp geomagnetic excursions have been reported in recent literature (McHargue et al, 1995). A mechanism which has been proposed for this enhancement, by these authors, is the change in galactic cosmic ray¯ux coincident with a supernova event.…”
Section: Resultsmentioning
confidence: 82%
“…In recent years, time-dependent models of the main geomagnetic ®eld going back to 1690 have been produced (Bloxham and Jackson, 1992), using which, long term (b 10 2 y) variations in cuto rigidities of cosmic rays can be computed. Enhanced cosmic ray production of 10 fe coincident with the Mono Lake and Laschamp geomagnetic excursions have been reported in recent literature (McHargue et al, 1995). A mechanism which has been proposed for this enhancement, by these authors, is the change in galactic cosmic ray¯ux coincident with a supernova event.…”
Section: Resultsmentioning
confidence: 82%
“…These results reveal elevated and very variable 14 C between 45 and 33 ka BP. These fluctuations may correlate with peaks in cosmogenic 36 Cl and 10 Be isotopes [20], which have been observed in polar ice cores, as well as those observed for 10 Be in marine sediments [1]. Modeling results suggest that the major features of this record cannot be produced with solar or terrestrial magnetic field modulation alone, but may require significant changes in the carbon cycle [c.f.…”
Section: Extension Of the Radiocarbon Time Scale To ~45000 Years Bpmentioning
confidence: 98%
“…Sample preparation involves dissolution of the sample and addition of 1-mg Be carrier, extraction of Be using acetylacetone, and ion exchange chromotography, as discussed by McHargue et al [1] Be(OH) 2 is precipitated from the final solutions and is converted to BeO by heating in air. The BeO powder is then mixed with a silver powder as a binder and the mixture is pressed into a Cu target holder for the AMS measurements.…”
Section: Some Ams 10 Be Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low geomagnetic field of the Laschamp event, which was first discovered in a lava flow of the Massif Central, France (Bonhommet and Zähringer 1969), and dated to ~40 ka cal BP (see Valet et al 2007 for a review) and more recently to 40.65 ± 0.65 ka cal BP (Singer et al 2009), has been discussed as the most likely cause of these changes. In the 1990s, measurements of 10 Be concentrations in deep-sea sediments became available showing enhanced 10 Be levels around 40 ka cal BP (McHargue et al 1995(McHargue et al , 2000Robinson et al 1995). Finally, reconstructions of geomagnetic field intensity in deep-sea sediments (Laj et al , 2002 and correlation with the ice-core record of cosmogenic isotopes 10 Be and 36 Cl has shown that the intervals of low geomagnetic field coincided with periods of increased flux of cosmogenic isotopes (Baumgartner et al 1998;Wagner et al 2000).…”
Section: Study Backgroundmentioning
confidence: 99%